Sound Insulation Properties of Malaysian Biomass Waste Fibre UF Composites - Nasidi, Ida Norfaslia; Ismail, Lokman Hakim; Samsudin, Emedya Murniwaty (International Journal of Integrated Engineering, 2022)
Natural fibre has a good capacity as acoustic insulation materials because of its characteristics, and therefore it is widely used in many applications. This research aims to explore biomass waste from the palm oil mill and coconut production as insulation materials. Fibre wastes used for this study included the empty fruit bunch (EFB), mesocarp fibre (MF) and coconut coir fibre (CF), which were treated using sodium hydroxide (NaOH) to eliminate excess oil and fibre surface impurities. The effect of the treatment was also considered to observe the effect towards the sound transmission loss (STL) performance of natural fibre. Three varying concentrations of NaOH (1%, 2% and 3%) were used to treat the fibre. The STL of EFB, MF and CF were measured using the impedance tube method with four microphones at frequencies from 160 Hz to 5,000 Hz. Pretreatment on EFB, MF and CF showed a decrement on the fibre diameter and changes on the fibre surface morphologies after examining using the scanning electron microscopy (SEM) analysis. The results showed that EFB, MF and CF treated fibre had higher STL performances than untreated fibre. The STL performances were increased by increasing the tested frequency from 160 Hz to 5,000 Hz. Changes in fibre morphology following the fibre pretreatment affected the STL performances of EFB, MF and CF. Additionally, treated MF using 2% of NaOH concentrations obtained the highest STL amongst all the test samples.